HUBUNGAN PELAYANAN ANC (Antenatal Care) DENGAN KEPUASAN IBU HAMIL DI BPS NIMAH MACHZYUMIJOMBANG - Adiesti, Ferilia (JURNAL KEPERAWATAN BINA SEHAT, 2016)
According to SUSENAS 2004, in general patients were satisfied with the health services available in private hospitals (70.9%), While that is feel less satisfied at getting traditional care at (56.6%). People who feel less satisfied when obtaining health services provided by the government by 50.5% and 47.9% Government Hospital (Research and Development Agency. Department of Health republic of Indonesia 2005). The research was aims to determine the ANC at the service relationship with satisfaction of Pregnant women at the Maternity Design of the study is correlational, Research variables that ANC services as an independent variable and satisfaction as the dependent variable pregnant women. samples used by 50 pregnant women purposive sampling technique using a questionnaire instrument. The results were tested using the Chi - Square.The results of cross tabulation showed that most get the standard of service by 32 respondents (64%). While most were satisfied with the services provided by 36 respondents (72%).Based on the results of Chi - Square = 10.77 X2hitungdata obtained and X2tabel= 3.84. So X2hitung> X2tabelRespondent research showed that the ministry of the ANC (Antenatal Care) provides a major influence on the satisfaction of pregnant women. It can be said that the better the service provided to the patient then the patient will automatically get satisfaction. Midwive to service provide, said to be good service if service provided in accordance with the standards of professional service.Key Words: Services ANC (Antenatal Care), Satisfaction Pregnancy